Respuesta :

Answer:

y = 2x + 3

Step-by-step explanation:

The y-intercept is clearly marked:  it's b = 3 (or 0, 3).

Going from the point (-3, -3) to the point (0, 3),

x increases by 3 and y increases by 6.  Thus, the slope of the line through these two points is m = rise / run = 6 / 3, or m = 2.

Starting with the slope-intercept form of the equation of a straight line:

y = mx + b, we substitute 2 for m and 3 for b, obtaining:

y = 2x + 3

Answer:

y = 2x + 3

Step-by-step explanation:

The equation of a line in slope- intercept form is

y = mx + c ( m is the slope and c the y- intercept )

Calculate m using the slope formula

m = (y₂ - y₁ ) / (x₂ - x₁ )

with (x₁, y₁ ) = (- 3, - 3) and (x₂, y₂ ) = (0, 3) ← 2 points on the line

m = [tex]\frac{3+3}{0+3}[/tex] = [tex]\frac{6}{3}[/tex] = 2

note the line crosses the y- axis at (0, 3) ⇒ c = 3

y = 2x + 3 ← equation of line